Estudo da bioacumulação de cobre e chumbo pela macrófita aquática Eicchornia crassipes em solução hidropônica - Szymanski, Nayara (2011)
Aquatic macrophytes are known to remove heavy metals from the surface by adsorption or absorption and incorporate them into systems, in different ways. The main objective of this work is to study the multicomponent bioaccumulation of copper and lead by the living aquatic macrophyte Eicchornia crassipes. The experiments were performed in triplicate using about 30g healthy young plants and 5L Clark s hydroponic solution doped with non-toxic concentration of copper and lead metals combined. All experiments have been carried out in a greenhouse, for 20 days, monitoring the loss of water volume and adding deionized water as it was needed. Samples were performed in predetermined collection times (2, 4, 7, 12 and 20 days) to determined the metal content by the synchrotron radiation reﬂection X-ray ﬂuorescence technique (SR-TXRF), and the measurements of SR-TXRF were performed at the Brazilian Light Synchrotron Laboratory (LNLS). It was observed that at least 90% metal concentration was removed of all experiments by bioaccumulation process, this indicates that the adsorption process is quick in roots, but slow if accumulation process takes place in aerial parts. The kinetics of biosorption that better fits the experimental data was Irreversible Langmuir for Cu and Pb, and Pseudo-first order and Pseudo-second order for Cu and Pb, respectively at the multicomponent experiment.